Characterization of thermal and mechanical properties of stanene nanoribbons: a molecular dynamics study. Issue 80 (30th October 2017) - Khan, Asir Intisar; Paul, Ratul; Subrina, Samia
Abstract : Thermal and mechanical properties of stanene nanoribbons have been characterized to aid the design of stanene based thermoelectrics and nanoelectronic devices. Abstract : Stanene, a buckled honeycomb structure of monolayer tin, has several intriguing electrical and thermoelectrical applications that closely depend on its thermal, mechanical, and electrical properties. However, thermal and mechanical characterizations of stanene nanoribbons (STNRs) have not yet been comprehensively investigated. In this study, we have performed an equilibrium molecular dynamics simulation to characterize the thermal and mechanical properties of STNRs using the modified embedded-atom method potential. The room temperature thermal conductivities of pristine 10 nm × 3 nm zigzag and armchair stanene nanoribbon were estimated to be 0.95 ± 0.024 W m −1 K −1 and 0.89 ± 0.026 W m −1 K −1, respectively. We also studied the thermal conductivity as a function of temperature and width of the ribbon. The thermal conductivity was found to decrease with increasing temperature, whereas it tends to increase with increasing width for both configurations. In all cases, the zigzag STNR exhibited a higher thermal conductivity than its armchair counterpart did. Furthermore, our study includes an investigation of the thermal transport in defected STNRs. For a defect concentration of ∼1.5%, the thermal conductivity of defected stanene nanoribbon experiences a reduction of approximately 30–50%, whereas a ∼70–90% reduction was observed at a vacancy concentration of ∼5% for various types of defects. Finally, the stress–strain behavior of STNRs with varying width was analyzed using uniaxial loading. Zigzag STNRs were found to have higher fracture strength than their armchair counterparts. Moreover, with increasing width, both fracture strain and fracture stress of armchair STNRs were found to show small variations compared with their zigzag counterparts. This study provides insights for tuning the thermo-mechanical characteristics of stanene-based nanostructures for thermal management and possible applications as thermoelectrics.